2007
DOI: 10.2320/matertrans.mra2007040
|View full text |Cite
|
Sign up to set email alerts
|

Grain Growth Behaviors in a Friction-Stir-Welded ZK60 Magnesium Alloy

Abstract: Grain growth during annealing of a friction-stir-welded (FSWed) ZK60 magnesium alloy has been investigated. We have found that (1) thermal stability exhibited in different parts of stirred zone (SZ) was very different, (2) grain growth was fairly abnormal, and (3) grain growth was directional and shapes of developed grains resembled flow patterns inherent to FSWed structure. We have shown that all peculiarities of the grain growth behaviors can be explained in terms of heterogeneous distribution of second phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Nevertheless, transmission electron microscopy (TEM) observations typically reveal high dislocation density in grain interiors [2,[8][9]. Limited experimental data evidence that the microstructure may contain a significant fraction of low-angle boundaries (30-35%) [10,11] and misorientation-angle distribution is characterized by an increased proportion of 30°boundaries [11]. The material in the central part of the SZ exhibits a very specific, h0 0 0 1i||welding direction, texture (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, transmission electron microscopy (TEM) observations typically reveal high dislocation density in grain interiors [2,[8][9]. Limited experimental data evidence that the microstructure may contain a significant fraction of low-angle boundaries (30-35%) [10,11] and misorientation-angle distribution is characterized by an increased proportion of 30°boundaries [11]. The material in the central part of the SZ exhibits a very specific, h0 0 0 1i||welding direction, texture (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Problems with the conventional fusion welding, limiting the use of the magnesium alloys, could be eliminated by friction stir welding (FSW), which is a solid state welding process [1]. Nowadays, FSW has been widely used to join the magnesium alloys, such as Mg-Al-Zn [2][3][4][5][6][7], Mg-Zn-Y [8,9], and Mg-Al-Ca [10].…”
Section: Introductionmentioning
confidence: 99%
“…3,4) Nevertheless, transmission electron microscopy (TEM) observations have typically revealed high dislocation density in grain interiors. [5][6][7] Limited experimental data have shown that the microstructure may contain significant fraction of low-angle boundaries (30 to 35%) 8,9) and misorientationangle distribution is featured by an increased proportion of 30-deg. boundaries.…”
Section: Introductionmentioning
confidence: 99%